2002
DOI: 10.17221/11854-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Soil moisture in mountain spruce stand

Abstract: Mountain forests are among the main components of natural environment in Slovakia. They grow mainly in areas with cold climate, on poor soils with unfavorable reaction, often very acidic (pH in H<sub>2</sub>O &lt; 4.5) and with nutrient deficit. Immissions and acid rain attack forests to a great extent. Global climate changes also represent a new threat. Extremes in air temperatures, excessive amounts of precipitation or on the other hand the lack of water from precipitation, torrential rains o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The coefficient of the SWRC calculation, using the algorithm published by [33], took into account a wide range of evaluated soil attributes (Table 5, Figure 5) for which we assumed a correlation with the natural phenomenon under evaluation. The overall calculation of LWRC values also included coefficients based on a study [2] on the volume of water retained by an SLS. Categories with a lower LWRC value of 1.5-6 have a low potential for retaining water in the landscape.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The coefficient of the SWRC calculation, using the algorithm published by [33], took into account a wide range of evaluated soil attributes (Table 5, Figure 5) for which we assumed a correlation with the natural phenomenon under evaluation. The overall calculation of LWRC values also included coefficients based on a study [2] on the volume of water retained by an SLS. Categories with a lower LWRC value of 1.5-6 have a low potential for retaining water in the landscape.…”
Section: Discussionmentioning
confidence: 99%
“…In total, there were 26 classes identified in the study area (Figure 4). An adjusted weighting coefficient was assigned to the elements of the SLS according to the work of [2] in terms of their significance for water retention capacity. The historical structures of the agrarian landscape were identified according to [36] and verified during a field survey in the years 2015-2017.…”
Section: Landscape Water Retention Capacity (Lwrc) Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…From the dry mass, the volume of water to add to reach the desired humidity level for each of the treatments was determined. The estimation of the optimal substrate water content was based on previous studies which showed that the optimal soil water content for spruce growth is between 60 and 80% of the maximum capillary capacity (Kutıĺek and Nielsn, 1994;Tuzǐnsky, 2002). Another similar study on Norway spruce used 60-80% of maximum capillary capacity for the control treatment, 40-59% of maximum capillary capacity for mild drought stress, and 20-39% of maximum capillary capacity for severe drought stress (Ditmarováet al, 2010).…”
Section: Experimental Designmentioning
confidence: 99%